On conditions for oscillation and nonoscillation of the solutions of a semilinear second-order differential equation
We establish sufficient conditions for oscillation and nonoscillation of regular solutions of the secondorder differential equation y’’ + p(t)|y|^1-λ |y’|^λ sign \